Analysis of the Greco-Roman world championships 2009 in Herning - Tünnemann, H. (2009)
1. Current tendencies in combat behaviour against the background of new competition rules 2009 2. Country-specific aspects of performance in competition 3. Qualitative analysis of combat behaviour 3.1 Combat behaviour of the nations 3.2 Combat behaviour of the winner 3.3 Technical-tactical developments after the rule changes 2009 in Greco-Roman Wrestling 4. Individual world top performances under technical-tactical aspects